Self-concept its relationship to achievement in chemistry of third year students at Ramon Avancena High School, Manila - Enriquez, Angelita L.
The relationship between the actual self-concept, ideal self-concept, self acceptance, and personal-social orientation of third year high school students of Ramon Avanceña High School in Manila and their achievement in chemistry is the focus of the study. It aims to determine how "high" achievers and "low" achievers in high school chemistry compare with respect to actual, personal-social orientation and how and to what extent these variables relate to achievement in chemistry.